1997
DOI: 10.1177/1069031x9700500405
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Export Success Factors of Small and Medium-Sized Canadian Firms

Abstract: In drawing attention to certain important gaps in the export marketing literature, this paper reports on a systematic study of critical factors for export success of small and medium-sized manufacturing firms in Canada. In this ethnocentric context, an attempt is made to investigate the presence of potentially significant differences in perceptions of key export success factors based upon export development, firm size, and product type. The study results point to the importance of the level of export developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 28 publications
4
30
0
2
Order By: Relevance
“…Other significant influences include the size of business measured as the number of employees which is consistent with the findings of Serra et al () in Portugal; Thompson and Zang () in the UK. In addition, consistent with there being a learning process associated with access to new markets (Katsikeas et al, ), the age of business is found to be positively related to export propensity. Moreover, firms that intend to increase sales over the next 3 years are more likely to export (De Clercq et al, ).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Other significant influences include the size of business measured as the number of employees which is consistent with the findings of Serra et al () in Portugal; Thompson and Zang () in the UK. In addition, consistent with there being a learning process associated with access to new markets (Katsikeas et al, ), the age of business is found to be positively related to export propensity. Moreover, firms that intend to increase sales over the next 3 years are more likely to export (De Clercq et al, ).…”
Section: Resultssupporting
confidence: 63%
“…Larger firms may have both greater financial and human capital, therefore the size of the business, as captured by the natural log of employment plus 1, is included (Serra, Pointon, & Abdou, 2012). Experience and understanding along with market reputation will also be built up over time, so the natural log of the age of the business plus 1 is also included (Katsikeas, Deng, & Wortzel, 1997).…”
Section: Controlsmentioning
confidence: 99%
“…According to Cavusgil and Zou (1994), export marketing strategy, competency in exporting, and commitment are the key determinants of export performance. Katsikeas et al (1997) found that the level of export development, product type, and to a lesser extent, company size influence export success. In addition to firm size, Baldauf et al (2000) found that management's motives to export and the use of a differentiation strategy are predictors of success.…”
Section: Competitiveness Factors For Exportingmentioning
confidence: 98%
“…Both the soft and the hard variables of the firm should apply to the measurement of performance. Since managers do not easily disclose the yearly average increase in profits from their export and overall business (Katsikeas et al, 1997), how well the firm functions in achieving overall and international corporate goals and objectives against defined standards defines overall and international business performance (Dolton et al, 1980;Cavusgil and Zou, 1994;Styles, 1998;Shoham, 1998).…”
Section: Measurement Of Variablesmentioning
confidence: 99%